TÍTULO: Morfologia hepática e perfil bioquímico sérico em Pygocentrus nattereri Kner(Characiformes: Serrasalmidae) - MARIA EDUARDA CORONA GARCIA (2022)
The Brazilian Pantanal is located in the Paraguay River basin with well-marked seasonal events, so it is an area with different resources that provides a diverse environment for fish. Pygocentrus nattereri is a fish from the Serrasalmidae family, popularly known as red piranha. It’s abundant in the Pantanal and is easily recognized by its morphological characteristics and feeding habit. In addition, the seasonal environment influences feeding and reproductive dynamics. Different types and food availability can result in changes in blood biochemical parameters, which generally have more instantaneous responses. Consequently, these changes are reflected in the liver, a central organ for nutritional metabolism. Furthermore, it is responsible for the storage of glycogen and lipids. Changes in the liver parenchyma and the density of structures can be quantified through histometric techniques, which allow estimating the area, volume, or amount of a given substance. Thus, this study aimed to describe and correlate hepatic morphological characteristics with the serum biochemical profile in Pygocentrus nattereri in different sexes and seasons.